Big Data Education Landscape for Graduates in Morocco: Insights from 2022 Offerings - Karim Ghanouane; Taoufik Benkaraache (Education Policy and Development, 2024)
The main objective of this research was to analyze graduate programs in Big Data in Morocco in 2022, focusing on the technical skills, tools and technologies, and functional skills taught in the programs. In the digital age, the Big Data revolution has generated massive amounts of data, transforming the way businesses and organizations around the world make decisions and innovate. In this ever-changing context, Training of Big Data professionals in Morocco in 2022 is crucial. The expansion of Big Data has created a growing need for skilled professionals to manage these immense data sets. Higher education programs play a key role in preparing these future experts. This study adopted a content analysis methodology, examining the curricula of 16 public engineering schools, and 21 accredited public schools and science faculties in Morocco. The technical skills, tools and technologies, and functional skills taught were analyzed and compared with existing literature on Big Data skills. The programs focus on technical skills such as programming, machine learning, statistics, and mathematics, with Python as the main tool. However, certain skills, such as predictive analysis, are under-represented. Functional skills in communication and management are essential; however, skills in agile methods and change management vary in coverage. The results offer an insight into the alignment between higher education programs and the needs of the Big Data market. Educational institutions can adjust their programs to better meet emerging needs, focusing on under-represented skills, and ensuring the continued relevance of training.